Design analysis and structural optimisation of a rigid ankle foot orthosis - Mohd Yashim, Wong Paul Tze (2018)
The ideal type of Ankle Foot Orthosis (AFO) for treating patients with lower limb impairments are those that closely follow the wearer’s anthropometry. Most mass-produced AFO that are available in the market does not cater the aforementioned requirements nonetheless it is cost-effective. Conversely, the existing AFO that does conform to individual anthropometry is expensive due to complex geometry, requiring skilled and experienced orthotist. Adding to this cost is the long lead time required to produce a unit of orthosis. In order to mitigate the aforementioned problems of mass produced and individual-specific AFO, this thesis proposes a methodological framework that addresses these issues from the design phase to the fabrication phase. This methodological framework aims to rectify the cost and complexity issue by integrating inexpensive solutions into the design and fabrication stage. In the design phase, a low-cost 3D scanning is adopted to obtain an accurate 3D capture of an individual’s anthropometry. An initial AFO prototype is modelled based on this 3D capture data through the use of a commercially available Computer Aided Design (CAD) software package, Autodesk Inventor. Subsequently a tensile test was performed to investigate different mechanical properties arising from varying printing parameters namely; material orientation, build density and print layer thickness of Zortrax Acrylonitrile Butadiene Styrene (ABS) material which is the material used in the fabrication stage employing the use of a low cost Zotrax M200 3D printer. This experimental investigation is not trivial as it provides significant insight on the mechanical characteristics of the varying parameters mentioned above. Based upon the experimental investigation, the best printing parameters were fed into the Finite Element Model to further investigate the structural integrity of the design as well as to carry out the proposed Topology Optimisation method. The evaluation of the structural integrity is important in order to weigh the feasibility of using the Fused Deposition Modelling (FDM) process in the manufacture of tailor made AFO. A structural optimisation is carried out to reduce the weigh and subsequently the cost of production without comprising the structural integrity of the AFO. From the study, by the implementing structural optimisation, specifically the topology method, the end design exhibits a cost reduction 3% and an actual improvement in structural integrity particularly the factor of safety from 0.289 before optimization to 4.671 after optimization suggesting a marked improvement. Therefore, this study has contributed to the body of knowledge by demonstrating that the proposed methodological framework is sound in the manufacture of individually customised AFO.